The five shades of oleylamine in a morphological transition of cobalt nanospheres to nanorods. Issue 25 (22nd June 2021) - Moisset, Arthur; Sodreau, Alexandre; Vivien, Anthony; Salzemann, Caroline; Andreazza, Pascal; Giorgio, Suzanne; Petit, Marc; Petit, Christophe
Abstract : Understanding of cobalt nanorods' (Co NRs) formation still remains challenging when it comes to enhancing their anisotropic properties applicable in magnetic or catalytic areas. Abstract : Understanding of cobalt nanorods' (Co NRs) formation still remains challenging when it comes to enhancing their anisotropic properties applicable in magnetic or catalytic areas. Herein, we propose a mechanism for the morphological transition from spherical cobalt nanoparticles (NPs) to Co NRs over time (9 h) in a mixture of [CoCl(PPh3 )3 ] and oleylamine (OAm). In the literature, we described how spherical Co NPs are synthesized via a disproportionation process. Based on in situ and pseudo in situ observations, two steps of this unique mechanism are characterized first by the dissolution of the spheres and then the regrowth in rods' shape in the presence of an OAm template. Furthermore, ex situ experiments show that these steps are the result of interdependent reactions occurring between Co NPs, cobalt(ii ) and OAm. The latter plays numerous roles in this synthesis: as a surfactant, a disproportionation promoter, and a hydrogen source allowing the reduction of cobalt(ii ) complexes; its ammonium salt derivative is involved in oxidative etching of Co NPs and it promotes the anisotropic growth in NRs. These coupling actions of reduction and etching generate two cobalt reservoirs of nuclei under thermodynamic conditions.